os vínculos entre o processo de aprendizagem e o desenvolvimento de competências de mulheres-empreendedoras - Vasconcelos, Rachel Costa Ramalho (2014)
The main objective in this study is to analyze the links between the learning process and the competence development of entrepreneur women. We tried to understand the role of context in the professional carrer of the entrepreneur women; to characterize the learning process; and to identify the entrepreneurial competences of BWSP winners. The theoretical base comprises four sections, in order to (a) present the different theoretical perspectives on the phenomenon of entrepreneurship; (b) to characterize entrepreneurial learning based on the construtivist-sociological approach and, therefore, experiential, including the RAE model (2004) and POLITIS (2005); (c) to address the entrepreneurial competence in a dynamic view, ie, as a result of professional action, taking into consideration the context and social experiences; and (d) to describe the links between learning and entrepreneurial competence from the learning process and the elements of the context which act as mediators on the development of competences. To facilitate the achievement of objectives, we used the method of oral history. The research was conducted with five BWSP winners, between the years of 2004 and 2012, in the small business category in the state of Paraiba. Data collection was made using a semi-structured interview which was transcribed and analyzed using narration analysis. Results show there are links between the learning process and the development of entrepreneurial competence by means of the context and its variables, which include economic and social conditions; family relationships; gender; and stereotypes. These variables affect the trajectory of entrepreneurs working lives. Besides, entrepreneurs highlighted that the process of entrepreneurial learning occurs in daily routine, through direct experiences, work practices, success and failure, and it is built from experiences. About entrepreneurial competence, entrepreneurs find it very important knowing how to identify business opportunities; knowing the activities and related business processes; moving resources in unforeseen situations; besides turning experiences into learning and willing to learn. Competence comes from some knowledge which is produced by experience and mediated by some context. The findings reveal that the development of entrepreneurial competence involves a continuous process of learning, while that learning reflects the competences, creating a virtuous circle. The learning process therefore underpins the development of competence. The survey results highlighted that the practices or experiences, social and family interactions, as well as self-development and contact with other people contribute to entrepreneurial identity and thus promote the links between learning and entrepreneurial competence